EVALUATION OF A NEW HIGH PERFORMANCE LIQUID CHROMATOGRAPHY BASED METHOD FOR VORICONAZOLE ANALYSIS IN BLOOD - Ambreen Rehman (Army Medical College Rawalpindi, 2019)
Objective: To develop and evaluate a new high-performance liquid chromatography (HPLC) based method for Voriconazole (VRC) analysis in blood.